A plate full of ready-to-relish pomegranate arils - Bhatia, Kavita; Asrey, Ram; Kannaujia, Pankaj Kumar (Indian Horticulture, 2019)
Pomegranate minimal processing saves time and adds comfort to consumers along with monetary benefits to growers and retailers. Thus, minimal processing offers a potential marketing opportunity for pomegranates. Readyto- eat arils, packed in polypropylene bags provide a shelf life of 15 days at 5 ± 2 °C and 85 ± 5% RH.